2016
DOI: 10.5430/jct.v5n2p13
|View full text |Cite
|
Sign up to set email alerts
|

Mediation as a Leadership Strategy to Deal with Conflict in Schools

Abstract: The concept of mediation is a process that is frequently used in the labour field and is under-developed in a field such as education. Mediation as a strategy to resolve conflict in an amicable way has gained support in various other fields but seems not to be seen as a mainstream solution to resolving conflict in education. This article reports on a qualitative study whose aim was to explore how the South African school principals deal with religious interest conflicts in their schools. The study employed nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…The findings concur with Ntho-Ntho and Nieuwenhuis (2016) who found that principals as leaders have a special role and moral obligation to reconcile disparate views of teachers and learners. School principals by virtue of their moral leadership role should monitor and oversee any programme that aims to bring change in the school by means of peer mediation.…”
Section: Findings and Discussionsupporting
confidence: 88%
“…The findings concur with Ntho-Ntho and Nieuwenhuis (2016) who found that principals as leaders have a special role and moral obligation to reconcile disparate views of teachers and learners. School principals by virtue of their moral leadership role should monitor and oversee any programme that aims to bring change in the school by means of peer mediation.…”
Section: Findings and Discussionsupporting
confidence: 88%